Reproductive performance of catfish Clarias sp. with probiotics Bacillus sp. NP5 addition through feed - Safira Qisthina Ayuningtyas; Muhammad Zairin Jr.; Widanarni (Jurnal Akuakultur Indonesia)
ABSTRACT